Analisis ruang lingkup serta sumber hukum administrasi negara untuk memahami implementasi sanksi administrasi negara - effendy, maidany (Maliki Interdisciplinary Journal, 2025)
This study aims to discuss the scope and division of legal sources in order to understand the implementation of various state administrative sanctions. This study uses a qualitative approach to describe the scope and division of administrative legal sources with various implementations of each state administrative sanction. The data collection technique used in this study is library research, which involves collecting various literature and analyzing it using the Miles & Huberman technique. Administrative law itself means everything that regulates the various tools or equipment that run the government, as well as the relationship between the government and its citizens. In addition, HAN also has two sources or foundations, namely material legal sources and formal legal sources. There are four types of HAN sanctions that can be applied to reduce the number of cases of violations against state administration, namely: government coercion, revocation of favorable decisions, imposition of coercive fines, and imposition of administrative fines.